Effects of garden visits on people with dementia: A pilot study. (May 2020) - Liao, Man-Li; Ou, Sheng-Jung; Heng Hsieh, Chung; Li, Zhelin; Ko, Chia-Chun
The number of people with dementia is increasing rapidly worldwide. Developing strategies to improve quality of life for those with dementia is crucial and is receiving more attention. Natural environments are known for their healing effects on most people. This pilot study aimed to understand the benefits that natural environments, such as gardens, can provide for people with dementia. In total, 42 staff members in nine dementia care facilities were recruited as participants in this study and answered a semistructured questionnaire. One-way analysis of variance with repeated measures and the Mann–Whitney U test were used to compare the effects of garden visits on evaluated characteristics and the differences in evaluated characteristics between free garden use and unfree garden use groups. Data from open-ended questions underwent text analysis to obtain the principal beliefs of the participants. The staff members reported that garden visits had positive effects on mood, social interaction, depression, and agitation in people with dementia because of the multisensory, gentle stimuli of the natural environment. Of the evaluated cognitive characteristics, attention and orientation to time were improved the most after residents with dementia had spent time in a garden. Additionally, staff members in the free garden use group scored the effects of garden visits on the mood, long-term memory, language abilities, spatial ability, aggression, and agitation of patients with dementia as significantly higher than staff members in the unfree garden use group. Recommendations for future studies are discussed.